Four-fermion contact interactions at one-loop and the new atomic parity violation results. - Gusso, A. (World Scientific Publ Co Pte Ltd, 2001)
We investigate the possibility that four-fermion contact interactions give rise to the observed deviation from the Standard Model prediction for the weak charge of cesium, through one-loop contributions. We show that the presence of loops involving the third generation quarks can explain such deviation.